Significance of Sarcopenia and the Neutrophil-to-Lymphocyte Ratio in Elderly Patients with Esophageal Squamous Cell Carcinoma - Huajian Peng; Xiang Tan (New Horizons in Medicine and Medical Research Vol. 10, 2022)
The purpose of this study was to explore the relation- ship between preoperative systemic inflammation, GNRI, PNI and sarcopenia in elderly ESCC patients and to eval- uate their correlation with the prognosis of ESCC patients. The clinical data of 121 elderly patients with ESCC were collected. The skeletal muscle area at the level of the third lumbar vertebrae (L3) was measured by computed tomography (CT), and then the skeletal muscle index (SMI) was calculated. Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated using univariate and multivariate Cox proportional hazards regression models. A total of 121 elderly ESCC patients were enrolled. Among them, 65 patients had sarcopenia. NLR, PNI and GNRI are significantly related to sarcopenia. The OS of ESCC patients with sarcopenia and/or NLR>2.24 was significantly worse. Survival analysis showed that patients with sarcopenia had significantly lower OS than those without sarcopenia (P<0.0001). It is concluded that sarcopenia was linked to PNI, GNRI, NLR, and PNI. Sarcopenia and NLR are separate prognostic variables for elderly ESCC, but they have a superior predictive value when they are combined.